Reducing the complexity of equilibrium problems and applications to best approximation problems - FODOR, Valerian-Alin; POPOVICI, †Nicolae (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
We consider the scalar equilibrium problems governed by a bifunction in a finite-dimensional framework and we characterize the solutions by means of extreme or exposed points. Mathematics Subject Classification (2010): 52A20, 41A50, 46N10, 90C33.